Risk Factors for Carbapenemase-Producing Enterobacterales Infection or Colonization in a Korean Intensive Care Unit: A Case-Control Study - Young Ah Kim; Se Ju Lee; Yoon Soo Park; Yeo Jin Lee; Jeong Hwa Yeon; Young Hee Seo; Kyungwon Lee (MDPI AG, 2020)
The purpose of this study is to identify the factors related to the infection and/or colonization of carbapenemase-producing Enterobacterales (CPE) based on clinical and microbiological data for patients in the intensive care unit (ICU). All patients admitted to medical ICU were screened for CPE on admission and weekly, and this 1:2 case-control study included patients with CPE identified by screening or clinical cultures from 2017 to 2018. The clonal relatedness was evaluated by pulsed-field gel electrophoresis (PFGE). A total of 45 CPE patients were identified with a prevalence of 3.8%. The most frequent organism was Klebsiella pneumoniae (69%) and the carbapenemases belonged to the class A Klebsiella pneumoniae Carbapenemase (KPC-2) (87%), class B New Delhi Metallo-β-lactamase (NDM) (11%), and Imipenemase (IMP-1) (2%) strains. The PFGE profiles showed two large clustered groups of KPC-2-producing K. pneumoniae. In the multivariate analysis, pneumonia/chronic pulmonary disease, previous fluoroquinolone use, and previous use of nasogastric tube were the significant risk factors for CPE infection or colonization in ICU-admitted patients. Critical illness and underlying medical conditions such as pneumonia/chronic pulmonary disease, antimicrobial selective pressure, and the use of a medical device are identified as risk factors for CPE infection or colonization in ICU. Person to person transmission also contributed.